Corporate Life Cycle on Real Earnings Management: Evidence From Indonesia - Paradisa Sukma (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2026)
This study examines the effect of the Corporate Life Cycle on Real Earnings Management (REM) in manufacturing companies listed on the Indonesia Stock Exchange during 2023–2024. The Corporate Life Cycle is classified into Introduction, Growth, Mature, Shake-out, and Decline based on Dickinson (2011), with Shake-out as the reference category. The sample consists of 205 firms with 410 firm-year observations. Multiple linear regression is employed using firm size, leverage, and profitability as control variables. The results indicate that the Mature stage has a significant positive effect on REM, while the Decline stage has a significant negative effect. The Introduction and Growth stages do not significantly affect REM. Firm size negatively affects REM, whereas leverage and profitability are insignificant. These findings suggest that REM practices vary across corporate life cycle stages.